Job opportunities and demands in relation to labor and supply from vocational courses of students in Isabela - Angoluan, Isabelita Alejandro 1940- (1982)
The purpose of this study was to determine the relation of job opportunities and demands to labor and supply from the vocational courses of students in Isabela.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Vocational education -- Philippines; Job vacancies -- Philippines; Isabela; Isabela